Peningkatan Model Pembelajaran Cooperatif Scripting dengan Keterampilan Proses untuk Meningkatkan Motivasi dan Hasil Belajar Kimia - Munandar, Haris; Najmah, Najmah; Kurniawati, Erga; Thayban, Thayban; Arviani, Arviani; Sukamto, Kostiawan (Universitas Negeri Gorontalo, 2022)
This Classroom Action Research aims to apply the Cooperative Scripting Learning Model to improve motivation and learning outcomes at SMA YP PGRI 2 Makassar. The research subjects were students of class XI IPA, totalling 35 students. The implementation of this research consisted of two cycles, each consisting of three meetings and one evaluation meeting. The learning outcomes that have been carried out have an increase in the category of student learning outcomes, in the first cycle in the medium category, namely 20 students or 57.14%, while in the second cycle, 17 people or 48.57%. The average increase in student motivation in cycle 1 was 60.57% and cycle II was 75.43%, as well as an increase in student learning mastery in cycle I, namely 24 people or 68.57% and an increase in cycle II as many as 31 people or 88, 57%. Thus, it can be concluded that the cooperative scripting biology learning model with process skills can increase the motivation and learning outcomes of class XI IPA SMA YP PGRI 2 Makassar.